Penerapan Kepatuhan Diit Untuk Mengatasi Ketidakseimbangan Nutrisi Pada Penderita Ulkus Diabetikum Di Magelang Jawa Tengah - Listyaningsih, Evi Dwi; Hidayah, Nurul; Margono, Margono (Universitas Muhammadiyah Magelang, 2023)
Diabetes Mellitus or what is known as blood sugar disease is a chronic disease of metabolic disorders whose incidence continues to increase every year. Diabetes Mellitus has a high risk of experiencing serious complications, one of which is diabetic ulcers. Patients with diabetic ulcers sufferers should pay attention to the application of dietary adherence to overcome nutritional imbalances. Patients with diabetic ulcers in carrying out the diet must pay attention the number of calories needed, the food schedule that must be followed, and the type of food that must be considered. The purpose of this case study is to compile a resume of nursing care for diabetic ulcer patients and to identify the application of dietary adherence to overcome nutritional imbalances in diabetic ulcer patients. The method used is descriptive research with a case study design through the nursing care process, namely assessment, nursing diagnosis, intervention, implementation, and nursing evaluation. Data collection techniques by observation, interviews, and blood glucose checks. This case study instrument uses a nursing assessment format, nursing kit, blood glucose level checking tool, and diary leaflet for diabetic ulcer patients. The results of the application of dietary compliance were given to 2 (two) diabetic ulcer patients for 2 weeks with 7 meetings, it was found that the nutritional imbalance could be resolved. In conclusion, the application of dietary adherence is useful for overcoming nutritional imbalances in diabetic ulcer patients.